Taxonomic synopsis of Leguminosae subfamilies Cercidoideae, Detarioideae, and Dialioideae in the National Forest of Caxiuanã, Pará, Brazil - de Carvalho, Catarina Silva; Pinto, Rafael Barbosa; Morim, Marli Pires; Santos, João Ubiratan Moreira dos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2021)
We conducted a floristic study in the National Forest of Caxiuanã (FLONA Caxiuanã) located in the state of Pará, Brazil, in the municipalities of Portel and Melgaço. This forest is characterized by  Amazonian physiognomies such as lowlands, seasonally flooded areas (várzea and igapó), Amazonian white-sand scrub (campinarana) and secondary forests. This article provides a taxonomic synopsis of the members of the Leguminosae subfamilies Cercidoideae, Detarioideae, and Dialioideae that occur in the FLONA Caxiuanã, based on herbarium studies and field expeditions. Nineteen species were catalogued, including two members of Cercidoideae, 16 of Detarioideae, and one of Dialioideae. The species of Cercidoideae from FLONA Caxiuanã are restricted to the Amazon forest, and one of them is exclusive to the Brazilian Amazon. Of the species of Detarioideae, 81.25% are restricted to the Amazon forest and 25% are exclusive to the Brazilian Amazon. The single species of Dialioideae is restricted to the Amazon forest. The most species-rich genera belong to Detarioideae: Macrolobium (six species). The two members of Cercidoideae and the only Dialioideae species occur in terra firme forest; the 56.25% species of Detarioideae occur in igapó forests. We include an identification key for the species presented in the synopsis, with illustrations, diagnoses, and taxonomic comments for all catalogued species.
Keywords: Amazon; Fabaceae; Flona; Flora; Taxonomy